A test of conditional independence against a tree order alternative for stratified data - Feng, Yanqin (Utilitas Mathematica, 2011)
Stochastic order among probability distributions has been widely studied. Likelihood ratio test is the most commonly used method to test hypotheses involving the various kinds of stochastic orders. This article gives a nonparametric test of conditional independence against a tree order alternative for stratified tables. Two real data sets will be applied to illustrate our theoretical result.